Impacts of global warming on summer precipitation trend over northeastern Eurasia during 1990–2010 using large‐ensemble experiments. (19th July 2022) - Kanamori, Hironari; Abe, Manabu; Fujinami, Hatsuki; Hiyama, Tetsuya
Abstract: Summer precipitation (June–August) increased markedly during the 2000s in Siberia, particularly in eastern Siberia. However, the nature of the mechanism that controlled this increase in precipitation remains under discussion. This study investigated the impacts of global warming on the trend of summer precipitation over northeastern Eurasia using large‐ensemble data from historical warming and nonwarming simulations for 1990–2010. Positive summer precipitation trends across Siberia reproduced in the ensemble mean of the historical simulation were similar to the observed data; however, negative trends observed over northeast China and Mongolia were not found in the ensemble mean. To extract members with a pattern of precipitation trend similar to that of the observations, empirical orthogonal function analysis was applied to the summer precipitation trend over Siberia for each simulation. The first leading mode in each simulation showed increase (decrease) in precipitation over eastern Siberia (northeast China), consistent with the spatial features of the observations. In the extracted members, the spatial pattern of the cyclonic (anticyclonic) circulation trend over northern parts of eastern Siberia (northeast China), associated with decadal and multidecadal variation, was amplified by global warming and resulted in an increasing trend of westerly moisture flux into eastern Siberia from western Siberia. Additionally, surface heating in northeast China, enhanced by global warming, might concurrently have intensified the cyclonic circulation over eastern Siberia. Furthermore, the results suggested that the reduced extent of Arctic sea ice coverage played a role in strengthening the cyclonic circulation over eastern Siberia and enhancing water vapour transport from the Arctic Ocean, which contributed to the strength of the westerly moisture flux over eastern Siberia. Although notable impacts of global warming on the precipitation trend in northeastern Eurasia were found, internal variation in the model experiments was also likely to have affected the precipitation trend, particularly in mid‐latitude regions. Abstract : The impacts of global warming on the trend of summer precipitation over northeastern Eurasia were investigated using large‐ensemble data from historical warming and non‐warming simulations for 1990–2010. The spatial pattern of the cyclonic (anticyclonic) circulation trend over northern parts of eastern Siberia (Northeast China), associated with decadal and multidecadal variation, was amplified by global warming, resulting in an increasing trend of moisture flux into eastern Siberia from western Siberia. Results suggested that the reduced extent of Arctic sea ice coverage played a role in strengthening the cyclonic circulation over eastern Siberia and enhancing water vapor transport from the Arctic Ocean, which contributed to the strength of the westerly moisture flux over eastern Siberia.